Faktor yang Mempengaruhi Minat Gen Z Berprofesi Sebagai Petani di Kecamatan Kotapinang - Riris Nadia Syafrilia Gurning; Cinta Soyakhna Harahap; Nana Trisna Mei Kabeakan; Juita Rahmadani Manik; Sakral Hasby Puarada (Universitas Medan Area, 2026)
This study aims to (1) Determine the perception of Gen Z in Kotapinang District towards the profession of farmer, (2) Determine the interest of Gen Z in Kotapinang District towards the profession of farmer, (3) Determine the factors that influence the interest of Gen Z in Kotapinang District in choosing a profession as a farmer. The method used is descriptive analysis to explain consumer characteristics, determine the perception of Gen Z and Gen Z's interest, and multiple linear regression analysis to determine what factors influence the interest of Gen Z in Kotapinang District to work as a farmer. The results of the study show that the characteristics of those participating in this study are Gen Z who have not worked or who do not have permanent jobs, and the majority of Gen Z who participated most in this study came from Kotapinang Village, and most respondents were female. The age of the respondents who participated most was 22 years old as many as 50 people, and the majority of respondents had a Diploma/Bachelor's degree. The results of the descriptive analysis also show that as many as 54% of Gen Z in Kotapinang District have a positive perception of the farming profession, in addition as many as 52% of Gen Z in Kotapinang District have a high interest in the farming profession. The results of the multiple linear regression analysis show that the factors that significantly influence Gen Z's interest in choosing a profession as a farmer are motivational factors, education level factors, and lifestyle factors. Meanwhile, income factors and social and community environmental factors do not significantly influence Gen Z's interest in choosing a profession as a farmer.